Investigating the quality of gender equality non-financial information disclosed in the cooperative credit sector: A case study - Olga Ferraro; Elena Cristiano (Journal of Risk and Financial Management, 2022)
Credit institutions, according to the 2014/95/EU Directive (implemented in Italy with Legislative Decree No. 254/2016) are obliged to report non-financial and diversity information. Our article focuses on the diversity information to investigate whether the obligation to disclose diversity information within the mandatory non-financial statement (NFS) led to an improvement of the quality of the gender equality information. To address this aim we analyzed five consolidated mandatory NFSs (CNFSs) for the Iccrea Cooperative Banking Group (ICBG) covering the 2017-2021 period. We selected ICBG because of the dearth of studies on the cooperative banking sector, which represent a relevant component of the national banking system in Italy. To the best of our knowledge, this paper is the first study to explore the quality of information on gender equality in mandatory NFSs for a cooperative banking group using a longitudinal approach. The analysis of the case study's findings provides evidence that ICBG worked to align its gender information with the Decree requirements and the GRI standards. The longitudinal analysis highlights that, during the five years under study, the ICBG's information on gender came to fully reflect the EU and Italian requirements.
Keywords: 650; gender diversity; Cooperative Credit Banks (CCBs); environmental and social and governance (ESG); non-financial statement (NFS)